THE ROLE OF GREEN SUKUK IN REALIZING THE SUSTAINABLE DEVELOPMENT GOALS 2030 AGENDA - Donna Vanny Araminta; Qudziyah Qudziyah; Yan Putra Timur (Universitas Airlangga, 2022)
The purpose of this study is to investigate green sukuk and its influence on the implementation of the Sustainable Development Goals (SDGs), as well as to identify and analyze the factors that have an effect on those activities. This research is carrying out a systematic literature review in order to locate, examine, and analyze any and all relevant research that is currently available in order to provide answers to the research questions. In spite of the fact that it is such a great innovative investment instrument and that it is doing well with getting positive response from the market, green sukuk still face many challenges, and there is still room for improvement to bring up its potentials and maximize its social impact for the most recent SDGs agenda. Green sukuk have developed into Islamic financial instruments that are in demand by the public because of their ethical responsibility towards the environment. Green sukuk provides benefits not only for all stakeholders involved in it but also for the environment. The government, as a regulator, is expected to be able to provide support through various strategic policies to support green sukuk, such as by developing a more substantial legal basis and incentives in the form of tax reductions, as well as strengthening information and literacy to the public about green sukuk.